INNOVATIVE ACTIVITIES IN THE HOTEL AND RESTAURANT BUSINESS - Horozhankina, N. A.; Razinkova, М. Yu.; Sabirov, O. V.; Mulenko, K. O. (Systems and Technologies, 2026)
The features of implementing innovations in the hotel and restaurant business are considered. The description of the “Khimik” hotel, which belongs to the category of two-star accommodation establishments, which provides a wide range of services of average comfort at affordable prices, is provided. It has been established that the organizational structure of the “Khimik” hotel is formed in accordance with the needs of a medium-sized enterprise and includes the main functional units that ensure effective management and guest service. Innovative activities in the “Khimik” hotel are implemented through the introduction of modern technologies aimed at improving service, effective management, saving resources and improving the quality of service. The hotel demonstrates a practical approach to innovation, focused on specific results. The innovative technologies implemented in the activities of the “Khimik” hotel are considered, which contribute to improving the quality of service, management efficiency and safety. It was observed that innovative activities at the “Khimik” hotel are an important component of the development strategy, allowing it to adapt to rapid market changes, increase the efficiency of internal processes and strengthen its position among competitors. Continuous improvement of the technological base and implementation of new innovative solutions opens up prospects for expanding the range of services, improving the level of service and meeting the growing needs of modern customers. A SWOT-analysis of the innovative activities of the “Khimik” hotel was conducted, identifying key internal advantages that ensure the effective implementation of modern technologies, in particular automated accounting systems, CRM and energy-saving equipment. At the same time, there are certain weaknesses, in particular, budget constraints and insufficient level of IT competence of the staff, which require attention for further development. External opportunities include the potential for expanding digital services, the introduction of new energy-saving technologies, and the growing demand for environmentally responsible service. At the same time, the hotel must consider threats in the form of increased competition, technical risks, changes in legislation, and economic instability. Based on the analysis, it is recommended to focus on improving staff skills, modernizing equipment, developing environmental initiatives, and strengthening cybersecurity. This will strengthen the hotel’s position in the market, improve the quality of service, and ensure the sustainable development of innovative activities.